Unraveling the influence of astrocytes on endothelial cell transcription: Towards understanding blood-brain barrier in vitro models’ dynamics - Laura Nicoleti Zamproni; Begüm Gökçe; Justina Venckute Larsson; Angela Ceballos-Torres; Magnus Gram; Marimélia Aparecida Porcionatto; Anna Herland (Brain Research Bulletin)
In recent years, considerable advancements have been made in developing in vitro models to better understand the complex dynamics of the blood-brain barrier (BBB) and its critical role in neurological health and disease. Incorporating astrocytes into these models introduces an essential layer of complexity, allowing for a more comprehensive investigation of the cellular interactions and regulatory mechanisms that maintain BBB integrity and functionality. Despite these advances, the specific influence of astrocytes on endothelial cells in in vitro systems remains inadequately explored. This study addresses this gap by examining the transcriptional changes in primary human brain microvascular endothelial cells (HBMECs) cocultured with human astrocytes (HAs). Our findings demonstrate that astrocytes profoundly modulate endothelial pathways involved in cell cycle regulation and division while upregulating genes associated with BBB integrity, protective mechanisms, and transporter activity. Furthermore, astrocytes significantly enhanced transendothelial electrical resistance (TEER) and reduced permeability to tracer Cascade Blue dye, confirming their functional impact on BBB models.By providing a comprehensive human primary cell dataset, this research underscores the pivotal role astrocytes play in shaping endothelial cell gene expression and function in contact coculture systems. These results emphasize the necessity of incorporating astrocytes into in vitro BBB models to accurately replicate neurovascular interactions. Ultimately, this study advances our understanding of BBB physiology and highlights the importance of refining in vitro models to better reflect the complexity of the human neurovascular environment, with potential implications for studying neurological disorders and drug delivery strategies.